2019
DOI: 10.1111/cns.13100
|View full text |Cite
|
Sign up to set email alerts
|

Negative regulation of glial Tim‐3 inhibits the secretion of inflammatory factors and modulates microglia to antiinflammatory phenotype after experimental intracerebral hemorrhage in rats

Abstract: Summary Aims To investigate the critical role of Tim‐3 in the polarization of microglia in intracerebral hemorrhage (ICH)‐induced secondary brain injury (SBI). Methods An in vivo ICH model was established by autologous whole blood injection into the right basal ganglia in rats. The primary cultured microglia were treated with oxygen‐hemoglobin (OxyHb) to mimic ICH in vitro. In this experiment, specific siRNA for Tim‐3 and recombinant human TIM‐3 were exploi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 41 publications
2
38
0
Order By: Relevance
“…4 Inflammation post-ICH, acknowledged by many researchers, plays a critical role in the breakdown of the blood brain barrier (BBB) and the late formation of PHE. 5,6,17 An in vivo study by SHIZHOU Lin and colleagues identified that leonurine could ameliorate PHE through attenuating BBB breakdown, reducing the inflammatory response and decreasing the amount of hemoglobin degradation, which maybe support our results to some extent. 5 The larger baseline hematoma volume triggers a more severe inflammatory response and leads to the extensive damage of BBB which conspire to create the DHE.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…4 Inflammation post-ICH, acknowledged by many researchers, plays a critical role in the breakdown of the blood brain barrier (BBB) and the late formation of PHE. 5,6,17 An in vivo study by SHIZHOU Lin and colleagues identified that leonurine could ameliorate PHE through attenuating BBB breakdown, reducing the inflammatory response and decreasing the amount of hemoglobin degradation, which maybe support our results to some extent. 5 The larger baseline hematoma volume triggers a more severe inflammatory response and leads to the extensive damage of BBB which conspire to create the DHE.…”
Section: Discussionsupporting
confidence: 82%
“…A recent review article detailed that a few days or weeks after sICH, the main cause of PHE is the release of hemoglobin degradation products after the red blood cells are dissolved; perhaps according to larger cerebral hemorrhage initial hematoma volume, the greater the toxicant secondary to the hemoglobin degradation more prone to cause the DHE . Inflammation post‐ICH, acknowledged by many researchers, plays a critical role in the breakdown of the blood brain barrier (BBB) and the late formation of PHE . An in vivo study by SHIZHOU Lin and colleagues identified that leonurine could ameliorate PHE through attenuating BBB breakdown, reducing the inflammatory response and decreasing the amount of hemoglobin degradation, which maybe support our results to some extent .…”
Section: Discussionmentioning
confidence: 99%
“…Concomitant with subsequent leukocyte infiltration, activated microglia augment the local production of proinflammatory cytokines, which amplifies blood–brain barrier (BBB) disruption and accelerates the expansion of perihematomal edema (PHE), resulting in more severe and durable brain injury . Although emerging evidence has implicated inflammation as a major component of PHE in the acceleration of brain injury following hemorrhage, the action of brain‐intrinsic factors in injury‐induced neuroinflammation remains poorly defined in ICH …”
Section: Introductionmentioning
confidence: 99%
“…The level of TGF‐β reflects microglial polarization after ICH. M1/M2 macrophage balance polarization is known to govern the fate of neuroinflammation and brain injury after ICH . Alternatively activated or M2 microglia/macrophages, which are polarized by cytokines such as IL‐4 and IL‐13, produce anti‐inflammatory cytokines such as IL‐10 and TGF‐β for neuroprotection, including inflammation suppression, tissue repair, remodeling, and vasculogenesis.…”
Section: Discussionmentioning
confidence: 99%